Metal‐Free Radical Borylation of Alkyl and Aryl Iodides - Cheng, Ying (Angew Chem Int Ed Engl, 2018)
A metal‐free radical borylation of alkyl and aryl iodides with bis(catecholato)diboron (B(2)cat(2)) as the boron source under mild conditions is introduced. The borylation reaction is operationally easy to conduct and shows high functional group tolerance and broad substrate scope. Radical clock experiments and density functional theory calculations provide insights into the mechanism and rate constants for C‐radical borylation with B(2)cat(2) are disclosed.